Notes towards an anthropological understanding of film narrative - Serra, Juan Pablo (2022)
This paper explores the value of interpreting film from an anthropological point of view, and takes a specific film as an example to put this thesis into practice. The ethical, aesthetic and pedagogical perspectives usually deferred to in courses on film appreciation and criticism are drawn together in an anthropological approach. Moreover, the paper argues that only an approach that encompasses some conception of the human person is capable of offering an explanation which makes sense of the different elements of a film. Finally, to address the anthropological perspective of a filmmaker necessarily involves reflection on the film critic’s view of the world.